Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Leverage, Arus Kas Bebas, Dewan Komisaris Independen dan Perencanaan Pajak Terhadap Manajemen Laba Pada Perusahaan Consumer Non-Cyclicals yang Terdaftar Di Bursa Efek Indonesia Periode Tahun 2019-2023 - Nuryana, Yayan; Murdianinsih, Dian (Jaanur Elbarik Indonesia, 2025)
This study analyzes the impact of managerial ownership, institutional ownership, leverage, free cash flow (FCF), independent commissioners, and tax planning on earnings management practices. Using a purposive sampling method, the research involved 75 non-cyclical consumer goods companies listed on the Indonesia Stock Exchange (IDX). The results indicate that managerial ownership and tax planning do not have a significant relationship with earnings management. Conversely, institutional ownership and leverage are proven to have a real influence. While FCF does not have a significant effect, the presence of independent commissioners is shown to influence earnings management. The coefficient of determination R2 of 97.2% demonstrates that these six variables collectively explain most of the variation in earnings management. This study emphasizes the critical role of corporate governance and financial structure in shaping earnings management practices among non-cyclical consumer goods companies in Indonesia..